If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 70 = 0 Reorder the terms: 70 + 7y = 0 Solving 70 + 7y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + 7y = 0 + -70 Combine like terms: 70 + -70 = 0 0 + 7y = 0 + -70 7y = 0 + -70 Combine like terms: 0 + -70 = -70 7y = -70 Divide each side by '7'. y = -10 Simplifying y = -10
| 3(x-4)=-21 | | x^2=-65 | | 2(6+2x)=8x | | 2a+3b+2c=32 | | 6x+2y=1 | | 2m-8=8 | | z^2+17z+52= | | 6x-5-3x=14+3 | | 3x-7=5+2x | | 2x-12=24 | | -2y-6=-8 | | -3a-12=3 | | 4x+13=-57-10x | | 5-5n=-20 | | -32-2x=13-7x | | 434443+0= | | 43444333+665564644= | | X^2+8x+84=0 | | 3(x-8)=5(-2x+11) | | 5x^2-12x+15=0 | | -5x+11=7x-19 | | (23x-23)-2=23 | | 2x^2-10x+12=0 | | 2x-4=34x | | 7x-2x=20 | | 6.4=4x | | 2x^2-x=4 | | 9v(8v^3)=0 | | n+8=10 | | 20a+12= | | 18s^2+25s-3=0 | | 3s^2+16s+5=0 |